Master track of Eugen Seibold cruise ES23C17, Panama City - Puerto Ayora, 2023-12-19 - 2023-12-28 - David Walter; Hans A Slagter; Hedy M Aardema; Lena Heins; Jana Härri; Antonis Dragoneas; Christopher Pöhlker; Ralf Schiebel (PANGAEA, 2026)
This dataset contains the validated master track of the S/Y Eugen Seibold during expedition ES23C17, with a time resolution of about 10 seconds. This master track can be used as reference for further expedition data. For creating the master track, the 1-second resolution raw data acquired by the GPS position sensor on board S/Y Eugen Seibold were processed, averaging latitude and longitude within equidistant 10-second intervals. Quality control was performed visually and by checking the maximum speed calculated between neighbouring positions. In case of unrealistically high speeds, data points have been removed.